From Law to Practice: Assessing Productive Waqf Governance Under Indonesia’s Law No. 41/2004 - Veronica, Cici; Arisandi, yosy; Afrianty, Nonie (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study examines the implementation of Law No. 41 of 2004 on Waqf at the Muhammadiyah Mosque in Bengkulu City, focusing on governance gaps between local waqf management and the Indonesian Waqf Board (BWI). A qualitative case study was employed, with data collected through semi-structured interviews (8 nazirs and BWI officers), document analysis (financial reports, meeting minutes), and participant observation (3 plenary meetings). Thematic analysis followed Miles and Huberman’s (2020) interactive model. Key issues include: (1) Exclusive planning (100% of meetings excluded BWI, violating Article 43); (2) Nazir incompetence (78% lack management training); (3) Low asset productivity (15–40% utilization rates); and (4) Weak supervision (no BWI oversight). The study highlights systemic non-compliance with national laws and Islamic governance principles (e.g., shura). Comparatively, Malaysia’s corporate waqf models achieve 85% efficiency, suggesting adoptable reforms. Institutional reforms—collaborative planning, nazir capacity-building, and tiered supervision—are critical to align waqf management with Shariah and legal mandates, unlocking its socio-economic potential.